"Introduction to Automata Theory, Languages & Computation" - Hopcroft (John E); Motwani (Rajeev); Ullman (Jeffery) (2006)
Automata Theory ; Language ; Computation
22.5
Keywords: Automata Theory ; Language ; Computation